20,000 Leagues Under the Sea - Church, Lisa R. 1960-; Verne, Jules 1828-1905. (New York : Sterling Pub., 2006)
The abridged adventures of a French professor and his two companions as they sail above and below the worlds oceans as prisoners on the fabulous electric submarine of the deranged Captain Nemo.
Keywords: Submarines (Ships) -- Juvenile fiction; Science fiction; Sea fiction